Ketersediaan Fasilitas yang Aksesibilitas bagi Penyandang Disabilitas di Kabupaten Bangkalan Madura - Sari, Dina Lusiana Novita; Pawestri, Aprilina (Fakultas Hukum Trunojoyo Madura, 2022)
ABTRACTThe rights of persons with disabilities are the same as normal human beings in general, so that in its fulfillment the government is prohibited from discriminating between them and even leading to acts of discrimination. Accessibility rights are part of the rights of persons with disabilities. However, these rights still escape the attention of the government, because they are considered not to be part of basic rights that must be made a priority. An example is in Bangkalan, Madura where the right of accessibility for persons with disabilities, especially in public facilities that should be disabled-friendly, is still not given much attention by the government. Therefore, the author is interested in studying how to fulfill the accessibility rights of persons with physical and sensory disabilities in Bangkalan Madura district. This study aims to find out how to fulfill the accessibility rights of persons with physical and sensory disabilities in Bangkalan Madura district.This research is a juridical-empirical research, using a statute approach. After conducting the research, it was found that accessibility in Bangkalan Regency public facilities was considered not yet friendly to persons with disabilities. Because the Government considers that it is more important to fulfill the basic rights of persons with disabilities first, such as the right to education, work, health and others.Keywords : Persons with Disabilities – Accessibility Rights – Basic Rights – Public Facilities